1995
DOI: 10.1063/1.115017
|View full text |Cite
|
Sign up to set email alerts
|

Surface ripples, crosshatch pattern, and dislocation formation: Cooperating mechanisms in lattice mismatch relaxation

Abstract: We study the interplay of elastic and plastic strain relaxation of SiGe/Si(001). We show that the formation of crosshatch patterns is the result of a strain relaxation process that essentially consists of four subsequent stages: (i) elastic strain relaxation by surface ripple formation; (ii) nucleation of dislocations at the rim of the substrate followed by dislocation glide and deposition of a misfit dislocation at the interface; (iii) a locally enhanced growth rate at the strain relaxed surface above the mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
54
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(60 citation statements)
references
References 0 publications
5
54
1
Order By: Relevance
“…[6][7][8][9][10] However, in the HgCdTe/CdZnTe epitaxial system (as well as other semiconductor systems), some of the strain energy is known to be released by other mechanisms, such as the formation of surface relief or crosshatch. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Consequently, the spacing of misfit dislocations at the interface may actually be significantly larger than the equilibrium spacing predicted by Eq. 2, assuming 100% of the elastic strain is released via the formation of misfit dislocations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[6][7][8][9][10] However, in the HgCdTe/CdZnTe epitaxial system (as well as other semiconductor systems), some of the strain energy is known to be released by other mechanisms, such as the formation of surface relief or crosshatch. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Consequently, the spacing of misfit dislocations at the interface may actually be significantly larger than the equilibrium spacing predicted by Eq. 2, assuming 100% of the elastic strain is released via the formation of misfit dislocations.…”
Section: Introductionmentioning
confidence: 99%
“…In some epitaxial systems, the stress concentration located in the valley regions of the crosshatch pattern can nucleate dislocation loops that grow to form misfit segments; however, other systems have been shown to form crosshatch patterns at the exclusion of misfit dislocations, while other systems have shown the opposite tendency, where misfit formation seems to be dominant over crosshatch formation. [19][20][21][22][23][24][25] In fact, the two strain-relief mechanisms may actually be competing mechanisms; both seeking to relieve the misfit strain in epitaxial growth of HgCdTe. Many excellent papers have been published on the topic of surface relief and crosshatch formation, and the details can be found there.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relaxation of low-strained layers ( < 2 %) usually takes place through misfit dislocations, and it is well known that the surface of these layers develops an undesired crosshatched morphology once the mechanisms for plastic relaxation start [3][4][5]. Furthermore, some studies on the low-mismatched SiGe/Si [6,7] and In x Ga 1-x As/InP (x  0.53) [8] systems have shown that the surface can also roughen prior to the generation of misfit dislocations and the subsequent crosshatch development. This surface roughening is associated with an elastic relaxation process and depends strongly on the growth kinetics.…”
Section: Introductionmentioning
confidence: 99%